Plants regulate the effects of experimental warming on the soil microbial community in an alpine scrub ecosystem - Ma, Zhiliang; Zhao, Wenqiang; Zhao, Chunzhang; Wang, Dong; Liu, Mei; Li, Dandan; Liu, Qing (PloS one, 2018)
Information on how soil microbial communities respond to warming is still scarce for alpine scrub ecosystems. We conducted a field experiment with two plant treatments (plant removal or undisturbed) subjected to warmed or unwarmed conditions to examine the effects of warming and plant removal on soil microbial community structures during the growing season in a Sibiraea angustata scrubland of the eastern Qinghai-Tibetan Plateau. The results indicate that experimental warming significantly influenced soil microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN), but the warming effects were dependent on the plant treatments and sampling seasons. In the plant-removal plots, warming did not affect most of the microbial variables, while in the undisturbed plots, warming significantly increased the abundances of actinomycete and Gram-positive bacterial groups during the mid-growing season (July), but it did not affect the fungi groups. Plant removal significantly reduced fungal abundance throughout the growing season and significantly altered the soil microbial community structure in July. The interaction between warming and plant removal significantly influenced the soil MBC and MBN and the abundances of total microbes, bacteria and actinomycete throughout the growing season. Experimental warming significantly reduced the abundance of rare taxa, while the interaction between warming and plant removal tended to have strong effects on the abundant taxa. These findings suggest that the responses of soil microbial communities to warming are regulated by plant communities. These results provide new insights into how soil microbial community structure responds to climatic warming in alpine scrub ecosystems.